2022
DOI: 10.3390/cancers14174167
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Derived Protein File from Peripheral Blood Predicts Immune-Related Adverse Events in Gastric Cancer Patients Receiving Immunotherapy

Abstract: Immune checkpoint inhibitors (ICIs) initiate a new stage for gastric cancer (GC) therapeutics, and plenty of patients have already benefited from ICIs. Liquid biopsy promotes the development of precision medicine of GC. However, due to the lack of precision biomarkers of immune-related adverse events (irAEs), the safety of ICIs-treated GC patients cannot be guaranteed. In our study, GC patients treated with ICIs were included for investigating the correlation between irAEs of ICIs and corresponding outcomes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For example, several studies have demonstrated that exosome‐derived PD‐L1 is a better indicator of disease and immune activity than plasma‐derived soluble PD‐L1. 35 , 36 Although only a limited number of studies have been conducted on using EV proteins to predict drug therapy‐induced AEs, 37 our research highlights the potential of EVs as biomarkers for predicting AEs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, several studies have demonstrated that exosome‐derived PD‐L1 is a better indicator of disease and immune activity than plasma‐derived soluble PD‐L1. 35 , 36 Although only a limited number of studies have been conducted on using EV proteins to predict drug therapy‐induced AEs, 37 our research highlights the potential of EVs as biomarkers for predicting AEs.…”
Section: Discussionmentioning
confidence: 90%
“…For example, several studies have demonstrated that exosome-derived PD-L1 is a better indicator of disease and immune activity than plasmaderived soluble PD-L1. 35,36 Although only a limited number of studies have been conducted on using EV proteins to predict drug therapy-induced AEs, 37 our research highlights the potential of EVs as biomarkers for predicting AEs. NF-κB signaling, which is elevated before durvalumab treatment in patients with symptomatic pneumonitis, is a master regulator of inflammation in lung endothelial cells.…”
Section: Discussionmentioning
confidence: 92%
“…PBS with 5% glycerol and 10 μg/ml of biotinylated bovine serum albumin (BSA) were used as negative and positive controls, respectively. The EV expression array assay was performed by referring to previous studies ( 13 , 14 ). Briefly, the microarray slides were incubated with a 10 μl unpurified plasma sample diluted (1:10) in wash buffer (0.05% Tween20 in PBS) at room temperature for 2 h followed by overnight incubation at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, Jiang et al. noticed the occurrence of irAEs corresponds to a better disease control rate of immunotherapy in gastric cancer patients ( 86 ). Even, patients with multiple irAEs had a trend toward improved PFS and OS, as compared with patients with only a single irAE ( 82 ).…”
Section: The Relationship Between Efficacy and Safetymentioning
confidence: 96%